‘Unheard,’ ‘uncared for’ and ‘unsupported’: The mental health impact of Covid -19 on healthcare workers in KwaZulu-Natal Province, South Africa - Dawood, Bilkis; Tomita, Andrew; Ramlall, Suvira (PLOS ONE, 2022)
As a direct consequence of the Covid-19 pandemic, due to being exposed to chronic and multiple sources of psychological stress, healthcare workers constitute a vulnerable population. Despite the potential impact of Covid-19 on their psychological and physical health, insufficient attention has been given to their mental well-being. The primary objective of this study was to measure and understand this psychological impact on public sector doctors and nurses in KwaZulu-Natal Province, South Africa. The secondary objective was to ascertain their perceptions of psychosocial support, specific to Covid-19, within the workplace. This cross-sectional electronic survey was conducted from August to October 2020, following the first surge of the pandemic in the country, and included 312 participants. Depression, anxiety and stress symptoms were assessed with the Depression Anxiety and Stress Scale-21 item and post-traumatic stress was measured by the Impact of Events Scale-Revised version. Measures of employer support were assessed using an adapted closed-ended questionnaire. The participants’ mean age was 36.6± 9.3 years with three quarters being male (n = 234, 75.0%) and predominantly (n = 214, 72.3%) medical doctors. Numbers of participants with depression, anxiety and stress were 121 (51.5%), 111 (47.2%) and 104 (44.3%) respectively, with 38 (16.2%), 50 (21.3%) and 38 (16.2%) in the combined severe/extremely severe range, respectively. On the Impact of Events Scale-Revised, 34 (13.7%) participants were in the severe range. Subjectively, 63.0% felt that their concerns were not ‘heard’, 75.1% did not feel ‘cared for’ and 81.1% and 74.0% did not feel ‘physically’ or ‘psychologically’ supported, respectively. High levels of depression, anxiety, stress and traumatic stress, combined with poor perceptions of employer support, highlight the need to identify and address the psychosocial support needs and expectations of healthcare workers for the duration of the pandemic, as well as for the mental health sequelae post-pandemic.